Again: methode(s) of Exegesis: Reflections on text and reality - Deist, Ferdinand (Old Testament essays, 1983)
The about-turn from historical-critical to immanent exegesis leaves us with the problem of the relationship between form. content and reality as well as with the problem of subjectivity inherent in linguistic studies. Neither the classical historical-critical nor the 'modern' immanent ap-proach to literature does justice to the complex phenomenon known as a text. Exegetical method should be distinguish-ed from recipes and procedures and viewed as post factum reasons for an interpretation arrived at through 8 much more complex mental activity.